Corporate governance and the nature of takeover resistance - Nicholas F. Carline; Scott C. Linn; Pradeep K. Yadav (University of Cologne, Centre for Financial Research (CFR), 2014)
We investigate the relation between corporate governance characteristics of hostile takeover targets and the choice to employ 'harmful' resistance that is not perceived as being motivated by shareholders' interests. We find that harmful resistance is associated with firms where managers have more pronounced ownership-based and age-related incentives for control, and directors have equity interests less aligned to stockholders. These firms also have less independent boards, are exposed to weaker discipline from outside blockholders, and are inferior performers. In the presence of harmful resistance, the market is less optimistic about the chances of bid completion, and there is a greater likelihood of managerial turnover.
Keywords: G34; 330; Takeover bid; Resistance; Corporate Governance; Stockholder returns; C.E.O. turnover